2009
DOI: 10.1038/emboj.2009.283
|View full text |Cite
|
Sign up to set email alerts
|

RNase Y, a novel endoribonuclease, initiates riboswitch turnover in Bacillus subtilis

Abstract: In contrast to Escherichia coli, initiation of mRNA decay in Gram-positive organisms is poorly understood. We studied the fate of the highly structured RNAs generated by premature transcription termination of S-adenosylmethionine (SAM)-dependent riboswitches in Bacillus subtilis. An essential protein of earlier unknown function, YmdA, was identified as a novel endoribonuclease (now called RNase Y) that was capable of preferential cleaving in vitro of the 5 0 monophosphorylated yitJ riboswitch upstream of the S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
365
1
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 219 publications
(395 citation statements)
references
References 39 publications
(78 reference statements)
27
365
1
2
Order By: Relevance
“…A model in which RNase Y processing occurs through a 6 nt (from the structure) ruler and cut mechanism was proposed. A similar scenario was previously observed in B. subtilis , where RNase Y processes the yitJ riboswitch, 6 nt upstream of the aptamer structure [12]. In speB mRNA, RNase Y processing events were 6 nt apart, however as mentioned above in a poorly structured region, and thus it would be unlikely that the ruler and cut mechanism by RNase Y is applicable for speB mRNA in S. pyogenes .…”
Section: Resultssupporting
confidence: 66%
See 3 more Smart Citations
“…A model in which RNase Y processing occurs through a 6 nt (from the structure) ruler and cut mechanism was proposed. A similar scenario was previously observed in B. subtilis , where RNase Y processes the yitJ riboswitch, 6 nt upstream of the aptamer structure [12]. In speB mRNA, RNase Y processing events were 6 nt apart, however as mentioned above in a poorly structured region, and thus it would be unlikely that the ruler and cut mechanism by RNase Y is applicable for speB mRNA in S. pyogenes .…”
Section: Resultssupporting
confidence: 66%
“…Although previous studies showed that RNase Y is sensitive to secondary structures located downstream of the processing events [10,12], a recent transcriptomic analysis in B. subtilis did not identify any consensus motif (neither sequence nor RNA structure) in proximity of RNase Y cleavages [39]. Our mutational study indicates that the sequence requirement ( i.e .…”
Section: Discussioncontrasting
confidence: 58%
See 2 more Smart Citations
“…31 RNase J belongs to the same family of enzymes (the β-CASP subgroup of the Zn-dependent metallo-β-lactamases) as the eukaryotic cleavage and polyadenylation factor CPSF-73. Intriguingly, this protein also forms a complex with a paralagous but catalytically inactive enzyme, CPSF-100, and is also thought to have 10,34 Depletion of this membrane-bound essential protein causes an even greater defect (>two-fold) in global mRNA decay rates than depletion of RNase J1/J2. Like RNase E, the endonucleolytic activity of RNase Y is dependent on the 5'-phosphorylation status of the RNA substrate.…”
Section: Role Of Rnase J In Other Organismsmentioning
confidence: 99%